1990
DOI: 10.1073/pnas.87.22.8820
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule dynamics in living dividing plant cells: confocal imaging of microinjected fluorescent brain tubulin.

Abstract: Carboxyfluorescein-labeled brain tubulin has been microinjected into stamen hair cells of Tradescantia, and its distribution during mitosis and cytokinesis was examined using confocal laser scanning fluorescence microscopy. The results show that brain tubulin incorporates into plant microtubules and is utilized throughout mitosis and cytokinesis. Microtubule structures that incorporate brain tubulin include the preprophase band, the perinuclear sheath at late prophase, the kinetochore fibers during prometaphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 29 publications
4
106
0
1
Order By: Relevance
“…We have used a blot overlay assay to study the interaction of KCBP with unpolymerized tubulin subunits. Bovine brain tubulin was used in all our blot overlay assays since (i) the amino acid sequence of tubulins is highly conserved between plants and animals (Fosket and Morejohn, 1992), (ii) microinjection of animal tubulin into plant cells results in incorporation of animal tubulin into different microtubule arrays (Hepler and Hush, 1996;Zhang et aL, 1990), (iii) microtubule pelleting assays showed binding of KCBP to animal microtubules (Reddy et al, 1996a), and (iv) in vitro motility studies have shown translocation of Arabidopsis KCBP on animal microtubules (Song et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We have used a blot overlay assay to study the interaction of KCBP with unpolymerized tubulin subunits. Bovine brain tubulin was used in all our blot overlay assays since (i) the amino acid sequence of tubulins is highly conserved between plants and animals (Fosket and Morejohn, 1992), (ii) microinjection of animal tubulin into plant cells results in incorporation of animal tubulin into different microtubule arrays (Hepler and Hush, 1996;Zhang et aL, 1990), (iii) microtubule pelleting assays showed binding of KCBP to animal microtubules (Reddy et al, 1996a), and (iv) in vitro motility studies have shown translocation of Arabidopsis KCBP on animal microtubules (Song et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In general, tubulins are COnseNed even between kingdoms (Fosket and Morejohn, 1992;Burns and Surridge, 1994). In fact, animal brain tubulin that is microinjected into living plant cells incorporates into the plant MT arrays (Zhang et al, 1990Cleary et al, 1992;Hepler et al, 1993). In addition to isotypic variation, many post-translationally modified isoforms of tubulin have been described (Greer and Rosenbaum, 1989; also see MacRae, 1992b;Ludueiia, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate mission of this bipolar MT array is to allow Golgi-derived vesicles to be transported unidirectionally toward MT plus ends so that the materials enclosed in these vesicles are deposited for the assembly of the cell plate. Phragmoplast MTs, like those MTs in spindles during mitosis, undergo continuous remodeling throughout cytokinesis [3,4]. Upon the completion of anaphase, MTs are polymerized and coalesced in the spindle midzone, and a bipolar array is established as the Kinesin-5 motor acts on anti-parallel MTs to slide them against each other ( Figure 1a) [5,6 ,7].…”
mentioning
confidence: 99%